Zielone zamówienia publiczne: instrument wspierania zrównoważonego rozwoju miast - Różowicz, Konrad (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2017)
The concept of sustainable development is an important element of the legal system of modern states. According to the concept of sustainable development, all the elements of the triad, society – economy – environment, should develop as evenly as possible. At the moment, the idea of sustainable development has its local dimension and as such should be a key component in the functioning of cities. One of the instruments to implement this concept are green public procurement. Supporting the environment through the implementation of public procurement allows to extend measures to achieve these objectives. Many cities have recognized the need to implement green public procurement so that it is possible to achieve the sustainable development.The concept of sustainable development is an important elementof the legal system of modern states. According to the concept of sustainabledevelopment, all the elements of the triad, society – economy– environment, should develop as evenly as possible. At the moment,the idea of sustainable development has its local dimensionand as such should be a key component in the functioning of cities.One of the instruments to implement this concept are green publicprocurement. Supporting the environment through the implementationof public procurement allows to extend measures to achieve theseobjectives. Many cities have recognized the need to implement greenpublic procurement so that it is possible to achieve the sustainabledevelopment.